PENGARUH BEBAN OPERASIONAL DAN PENDAPATAN TERHADAP LABA BERSIH - sepurrohman, yoga (Universitas Muhammadiyah Tangerang, 2023)
The purpose of this research determines the effect of operating income and expenses on net income. The variables used in this reasearch are income, operating expenses and net income. The research method is to use quantitative methods with a non-parametric statistical approach because the sample less than 30 it just 7. Data analysis techniques used were correlation analysis, multiple linear multiple regression and coefficient of determination. The hypothesis testing technique uses a contingency coefficient test. Based on the results of the data analysis test, it shows that income and operating expenses affect net income with a value of 2count (30,000) greater than 2table (14,067) then at an error rate of 5% it was decided to reject H0 so that H2 is accepted because the significance value is 0.224 and greater than 0.05 95% confidence level so that income and operating expenses have a simultaneous effect on net income by the contribution or influence of income and net income of 65.3% to net income from the results of the analysis of the coefficient of determination.